On Vector-Valued Generalized Lorentz Difference Sequence Space. (21st September 2014) - Sağır, Birsen; Oğur, Oğuz
Abstract : We introduce generalized Lorentz difference sequence spacesd ( v, Δ, p ) . Also we study some topologic properties of this space and obtain some inclusion relations.